Oliver - Hoff, Syd, 1912-2004. (New York : Harper, 1960)
Oliver looks elsewhere for employment after learning that the circus already has enough elephants.
180
Accelerated Reader AR
Keywords: Elephants -- Fiction; Circus -- Fiction